HUBUNGAN ANTARA MOTIVASI BELAJAR SISWA DENGAN HASIL BELAJAR SISWA - Kristin Simorangkir, Eka; Pangestie, Esty Pan (Jurnal Bimbingan dan Konseling Pandohop, 2022)
Motivation to learn is what is needed to develop one's potential optimally and be able to do better, achieve and be creative. Therefore, learning motivation in students is very important to arouse enthusiasm in students in learning to achieve success. Learning outcomes are an achievement or achievement obtained by students accompanied by a change in behavior in learning activities. Learning outcomes can be in the form of knowledge abilities, skills, attitudes and behavior after learning. The purpose of this research is to find out whether there is a relationship between learning motivation and student learning outcomes at Palangka Raya Christian High School in 2021/2022. This type of research is quantitative research with correlational or relationship quantitative methods. The population in this study were students of class X and XI with the sample members taken as much as the population in this study, namely 73 students. Data collection techniques used are, questionnaires, observations, and documentation. The data analysis technique in this study uses product moment correlation. Based on the results of the study, it was found that as many as 12 students or 16.43% had sufficient learning motivation, 46 students had sufficient learning motivation, and 15 students had poor learning outcomes. There is a relationship between learning motivation and learning outcomes as evidenced by the obtaining of an rxy of 0.343 which is in the low category. Then the t-test was carried out and the value of tcount > table = 3,076 > 2,000, so that H0 was rejected and Ha was accepted. This shows that "There is a relationship between learning motivation and student learning outcomes of Palangka Raya Christian High School in 2021/2022".